Attendance system using Mykad and mobile application - Mastura, Awang (2010)
MyKad or Government Multipurpose Card (GMPC) is the initiative of the Malaysian Government in providing the public with added convenience on the single smart card. Personal Digital Assistant (PDA) also known as a palmtop computer.It used to store information that can be accessed at anytime and anywhere.Attendance System using MyKad and Mobile Application (ASMMA) is developing for Sekolah Menengah Sultan Mansor (SMSM).The system is a prototype of attendance system that allows the system record time check in and checkout using MyKad.The system also helps principal view the daily attendance report through PDA. in order to manipulate the advantages of GMPC features and advantages of PDA, ASMMA is developing to overcome problem since the process to manage the staff's attendance is still done manually.The problem that may during the key in data process it will take a lot of times and requires in order recording the data into the database.Automatically,ASMMA record check in/out time and allow key in their reason for coming late or absent.ASMMA is expected will minimize the time saving during the attendance process.